Mediating identity through orality in West African films adapted from literature - Chibogu, Kenechukwu (Centre for Film and Media Studies, 2024)
This work critically examines the complexity of the ways by which filmmakers are mediating oral tradition forms as secondary orality in West African Films. The study aims to show that filmmakers mediate orality as an aesthetic source. The goal is to examine the value of the oral narrative on the screen. To study the oral qualities of the literature in the audio-visual primarily because of its aesthetic and stylistic feature in the narrative by interrogating the oral aestheticsin African films. To analyze the mediation of oral tradition in films, I combine orality theory, adaptation theory, and postcolonial theory to develop a model that treats film theoretically as ‘secondary orality adaptation (SOA)', which is interpreted using textual analysis in films such as Xala (1975), Karmen Gei (2001) and Invasion 1897 (2014). In the process, the study has explicitly engaged the aesthetic value of ‘orality' within the ambit of film studies thatrecognizes its wide reach and filmmakers' mediation and agency in the construction of identityusing the audio-visual method. The study finds that each mediation process involving oral tradition forms in West African films adapted from literature adds to the understanding of howfilm functions as a secondary orality adaptation. Whereas some filmmakers endorse cultural practices, others promote protest and contestation metaphorically using filmic codes (aural narratives) that are understandable to audiences and employ language as orality to construct identity in contemporary African postcolonial societies.